pH Stress-Induced Cooperation between Rhodococcus ruber YYL and Bacillus cereus MLY1 in Biodegradation of Tetrahydrofuran - Liu, Zubi; He, Zhixing; Huang, Hui; Ran, Xuebin; Oluwafunmilayo, Adebanjo O.; Lu, Zhenmei (Frontiers in Microbiology, 2017)
Microbial consortia consisting of cooperational strains exhibit biodegradation performance superior to that of single microbial strains and improved remediation efficiency by relieving the environmental stress. Tetrahydrofuran (THF), a universal solvent widely used in chemical and pharmaceutical synthesis, significantly affects the environment. As a refractory pollutant, THF can be degraded by some microbial strains under suitable conditions. There are often a variety of stresses, especially pH stress, that inhibit the THF-degradation efficiency of microbial consortia. Therefore, it is necessary to study the molecular mechanisms of microbial cooperational degradation of THF. In this study, under conditions of low pH (initial pH=7.0) stress, a synergistic promotion of the THF degradation capability of the strain Rhodococcus ruber YYL was found in the presence of a non-THF degrading strain Bacillus cereus MLY1. Metatranscriptome analysis revealed that the low pH stress induced the strain YYL to up-regulate the genes involved in anti-oxidation, mutation, steroid and bile acid metabolism, and translation, while simultaneously down-regulating the genes involved in ATP production. In the co-culture system, strain MLY1 provides fatty acids, ATP, and amino acids for strain YYL in response to low pH stress during THF degradation. In return, YYL shares the metabolic intermediates of THF with MLY1 as carbon sources. This study provides the preliminary mechanism to understand how microbial consortia improve the degradation efficiency of refractory furan pollutants under environmental stress conditions.